Tunable Filters Using Defected Ground Structures at Millimeter-Wave Frequencies - Kaushik Annam; Birhanu Alemayehu; Eunsung Shin; Guru Subramanyam (Micromachines)
This paper explores the potential of phase change materials (PCM) for dynamically tuning the frequency response of a dumbbell u-slot defected ground structure (DGS)-based band stop filter. The DGSs are designed using co-planar waveguide (CPW) line structure on top of a barium strontium titanate (Ba0.6Sr0.4TiO3) (BST) thin film. BST film is used as the high-dielectric material for the planar DGS. Lower insertion loss of less than −2 dB below the lower cutoff frequency, and enhanced band-rejection with notch depth of −39.64 dB at 27.75 GHz is achieved by cascading two-unit cells, compared to −12.26 dB rejection with a single-unit cell using BST thin film only. Further tunability is achieved by using a germanium telluride (GeTe) PCM layer. The electrical properties of PCM can be reversibly altered by transitioning between amorphous and crystalline phases. We demonstrate that incorporating a PCM layer into a DGS device allows for significant tuning of the resonance frequency: a shift in resonance frequency from 30.75 GHz to 33 GHz with a frequency shift of 2.25 GHz is achieved, i.e., 7.32% tuning is shown with a single DGS cell. Furthermore, by cascading two DGS cells with PCM, an even wider tuning range is achievable: a shift in resonance frequency from 27 GHz to 30.25 GHz with a frequency shift of 3.25 GHz is achieved, i.e., 12.04% tuning is shown by cascading two DGS cells. The results are validated through simulations and measurements, showcasing excellent agreement.